Multigene phylogeny and morphology reveal a new species, Ophiocordyceps tettigonia, from Guizhou Province, China - Wen, Ting-Chi; Xiao, Yuan-Pin; Zha, Ling-Sheng; Hyde, Kevin D.; Kang, Ji-Chuan (Phytotaxa, 2016)
A species of Cordyceps sensu lato associated with an adult of Tettigonia was collected in Chishui Danxia natural world heritage site, Guizhou Province, China. Following morpho-phylogenetic studies it was found to be a new species and is described as Ophiocordyceps tettigonia sp. nov. It differs from similar Ophiocordyceps species in having a unique host insect, and wide secondary ascospores. Combined sequence data from the ITS, SSU, TEF, and RPB1 gene loci also confirmed the distinctiveness of this new species.